The association between nutritional risk and survival time among patients with pancreatic cancer following pancreaticoduodenectomy: a retrospective cohort study - Tian, Qiuju; Su, Jing; Chen, Leying; Zhang, Min; Wu, Beiwen; Shen, Baiyong (Frontiers in Oncology, 2025)
BackgroundNutritional problems are common in patients with pancreatic cancer. However, the relationship between nutritional risk screening and the survival of patients after pancreaticoduodenectomy remains inconclusive. This study aimed to examine the association between preoperative nutritional risk and survival time among adult Chinese patients with pancreatic cancer after pancreaticoduodenectomy.MethodsThis study was conducted at Ruijin Hospital, affiliated with Shanghai Jiao Tong University School of Medicine in China. Patients aged 18 years or more who received pancreaticoduodenectomy for pancreatic cancer in our center between December 2019 and June 2022 from the follow-up database were included in the study. We retrospectively collected data on the demographics, disease, treatment, nutritional risk score, and survival time of the patients with pancreatic cancer. A Cox regression model was used to analyze the association between nutritional risk and survival time in different covariate models.ResultsA total of 656 patients were included in the study, and the median survival time was 24.0 months (95% CI:21.6-26.3). In total, 29.1% of patients had nutritional risk on admission. At the end of the follow-up, a total of 364 (55.5%) patients had died. The overall 1-, 2-, and 3-year survival rate of the 656 patients with pancreatic cancer after pancreaticoduodenectomy was 72.7%, 49.8%, and 34.4%, respectively. In the Cox regression model adjusted for age, education level, carbohydrate antigen 199 levels, neutrophil-lymphocyte ratio, tumor diameter, lymph node metastasis, distant organ metastasis, differentiation, nerve invasion, surgical margins, surgical time, intraoperative blood loss, postoperative complications, and chemotherapy, patients with nutritional risk score greater than 3 had a lower survival time compared with those without nutritional risk (HR = 1.33, 95% CI:1.06–1.67; P = 0.015).ConclusionsPreoperative nutritional risk has a detrimental impact on survival in patients with pancreatic cancer who undergo pancreaticoduodenectomy, and this relationship is stable. Nursing staff should screen early for nutritional risk using the Nutritional Risk Screening-2002 tool in patients with pancreatic cancer at diagnosis and, in conjunction with their doctors, develop and implement a timely nutritional treatment plan for those at risk to improve the poor survival time.